A Longitudinal Study of the Long-Term Predictors of China's Divorce Rate. Issue 3 (2nd April 2020) - Mo, Li
Abstract: Based on data from the China Statistical Yearbook from 1996 to 2013, this study explores the long-term predictors of China's divorce rate over recent decades with the longitudinal models incorporating the repeated measure models and long-term change models. The research findings suggest that among the factors researched, the economic development and the time factor are the two most essential predicators explaining the long-term variations in China' divorce rate from 1996 to 2013. This result provides additional empirical evidence from China as a transitional economy to support the widely accepted assumption that the divorce rate rises with the advance of modernization. On the contrary, the positive effect of women's empowerment disappeared with the presence of economic development, indicating that over a long period of time, the two factors do not work at the same time, and the economic development may affect the divorce rate independent of the influence of women's empowerment. It can be implied that despite calls for the revival of Chinese tradition and culture under Xi Jinping's rule since 2012, China's divorce rate is expected to continue to rise with further economic development.